Dendrimer encapsulated gold nanoparticles as catalyst precursors for oxidative transformations of unsaturated hydrocarbons - Slazus, Ene (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.